2021
DOI: 10.3390/ijms22105291
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of nsLTP Gene Family and Identification of SiLTPs Contributing to High Oil Accumulation in Sesame (Sesamum indicum L.)

Abstract: The biosynthesis and storage of lipids in oil crop seeds involve many gene families, such as nonspecific lipid-transfer proteins (nsLTPs). nsLTPs are cysteine-rich small basic proteins essential for plant development and survival. However, in sesame, information related to nsLTPs was limited. Thus, the objectives of this study were to identify the Sesamum indicum nsLTPs (SiLTPs) and reveal their potential role in oil accumulation in sesame seeds. Genome-wide analysis revealed 52 SiLTPs, nonrandomly distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…Lipid transfer proteins (LTPs) from L. usitatissimum , T. pratense , and S. indicum have been primarily studied via transcriptomics rather than as mature peptides [ 32 , 33 , 34 , 35 ]. LTPs accounted for 13 of 22 Cys-rich AMPs identified across the three seed extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid transfer proteins (LTPs) from L. usitatissimum , T. pratense , and S. indicum have been primarily studied via transcriptomics rather than as mature peptides [ 32 , 33 , 34 , 35 ]. LTPs accounted for 13 of 22 Cys-rich AMPs identified across the three seed extracts.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have shown that plant nsLTP genes play an important role in the response to biotic and abiotic stresses and in plant growth and development [ 11 , 18 , 21 , 23 , 25 , 28 , 29 , 31 ]. To date, with the availability and feasibility of plant reference genomes, the nsLTP gene family has been identified at the genome-wide level in various plant species, including Arabidopsis, Gossypium , sesame, cotton, wheat, potato, tomato, tobacco, barley, maize, cabbage and Chinese cabbage [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 58 , 59 , 60 , 61 ]. In this study, 283, 127, 151 and 106 nsLTP genes were identified in B. napus , B. rapa , B. oleracea and A. thaliana genomes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The model dicot Arabidopsis has been reported to contain 79 nsLTP genes [ 42 ]. Studies showed that there are 77 in rice [ 42 ], 63 in maize [ 42 ], 58 in sorghum [ 42 ], 461 in wheat [ 43 ], 70 in barley [ 44 ], 63 in B. rapa [ 45 ], 89 in cabbage [ 46 ], 83 in potato [ 47 ], 64 in tomato [ 48 ], 51 in Gossypium arboretum [ 49 ], 47 in G. raimondii [ 49 ], 91 in G. hirsutum [ 49 ], 52 in sesame [ 50 ] and 64 in Arachis duranensis [ 51 ]. To date, there has been no systemic whole-genome analysis of the nsLTP gene ( BnLTPs ) family in B. napus under various abiotic/biotic stresses, as well as in seed development and germination, and seed coat color formation, although the reference genomes of different cultivars or ecotypes of B. napus have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Gene duplication is considered one of the key evolutionary drivers of genes and genomes, providing raw genetic materials for the origin of physiological or morphological novelties [52,53]. Three types of gene duplication events can occur during organismal evolution: segmental duplication, tandem duplication, and transposon-mediated retroposition [54]. Tandem duplication is more common in the gene family expansion of diploid animals than in that of plants, resulting in a series of homologous genes closely arranged in the same or adjacent genomic regions [52].…”
Section: Molecular Characteristics and Evolutionary Pattern Of Aaap Transporters In Bphmentioning
confidence: 99%
“…Determining the spatiotemporal expression pattern is vital for elucidating the functional roles of genes [54]. In this study, the transcriptional expression of putative AAAP family members was profiled at 15 different life stages and in six different BPH tissues (Figure 5a,b).…”
Section: Spatiotemporal Expression Pattern Of Aaap Transporter In Bphmentioning
confidence: 99%